Les Élections du 12 décembre 2019 en Irlande du Nord : La partition, question centrale ? - Michel Savaric (Revue Française de Civilisation Britannique)
Until the referendum of 23 June 2016, Northern Ireland, as seen from London, could appear to be a settled matter. Since 2007, it had been jointly managed by the two historic enemies, the DUP and Sinn Féin, and the institutions provided for in the 1998 power-sharing agreement were functioning smoothly. But the predominantly English vote in favour of Brexit upset a balance that had remained relatively fragile. The result brought to the forefront the issue of the partition of Ireland, as reflected in the border dividing it into two jurisdictions and dividing the population in the North over its legitimacy. Coincidentally, the snap general election called by Theresa May in 2017 had given the DUP, the party founded by Ian Paisley, a decisive role. Indeed, it was the opposition of the 10 Unionist Democratic MPs to any differential treatment for Northern Ireland that had blocked the implementation of Brexit and provoked another snap election in 2019. The political impasse also coincided with the centenary of the Irish War of Independence and the 50th anniversary of the civil rights movement and the outbreak of the Troubles. It is therefore important to analyse the election of 12 December 2019 in Northern Ireland in relation to the political upheavals in Westminster, with the issue of the physical border and the Backstop involving the European Union and the Republic of Ireland. While these ongoing controversies have rekindled age-old divisions, it will also be seen that a growing proportion of the Northern Irish population is seeking to escape the traditional dichotomy between orange and green.